2014
DOI: 10.1103/physrevd.89.083517
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constraints on interacting dark energy with redshift-space distortion after Planck data

Abstract: The interacting dark energy model could propose a effective way to avoid the coincidence problem. In this paper, dark energy is taken as a fluid with a constant equation of state parameter wx. In a general gauge, we could obtain two sets of different perturbation equations when the momentum transfer potential is vanished in the rest frame of dark matter or dark energy. There are many kinds of interacting forms from the phenomenological considerations, here, we choose Q = 3Hξxρx which owns the stable perturbati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 194 publications
3
68
0
Order By: Relevance
“…In particular, to alleviate the coincidence problem, an interaction between dark energy and dark matter has been considered extensively in the literature, for example, in [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and references therein. However, usually the interaction form has to be assumed.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, to alleviate the coincidence problem, an interaction between dark energy and dark matter has been considered extensively in the literature, for example, in [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and references therein. However, usually the interaction form has to be assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, from observational point of view, recent data favor the late time interaction between DM and DE [18][19][20][21][22][23]. Also the coupling parameter in the interaction can be measured by various observations [21][22][23][24][25][26][27][28][29][30]. Moreover, it is speculated that class of interacting dark fluid models may resolve the current tensions on σ s and the local value of the Hubble constant H 0 [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Also the coupling parameter in the interaction can be measured by various observations [21][22][23][24][25][26][27][28][29][30]. Moreover, it is speculated that class of interacting dark fluid models may resolve the current tensions on σ s and the local value of the Hubble constant H 0 [22][23][24][25][26][27][28][29][30][31]. Additionally, cosmologists are of the opinion that the interaction between the dark sectors may leave an imprint on the perturbation analysis and as a result there may be significant changes in the lowest multipoles of the CMB spectrum [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The constraint results presented that the mean values of interaction rate was ξ x = −0.61 + 0.12 − 0.25 at 1σ level. The constraint results of energy exchange Q = 3Hξρ x from CMB, BAO, SNIa, Redshift-space distortions (RSD) [69] have shown that the interaction rate was the order of 10 −3 at 1σ level, there was no evidence for the coupling between dark energy and dark matter [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%